True Love as a Boundary Breaker of Culture in Chetan Bhgat’s 2 States: The Story of My Life - Paudel, Rudra Prasad (Journal of English Language and Literature (ISSN: 2368-2132), 2015)
This article tries to demonstrate the power of spiritual love in Chetan Bhagat’s autobiographical novel 2 States: The Story of My Life. Love is universal. It is a force for making the unity among people. The eternal power of love assimilates different cultures, castes, classes and traditions, and creates a harmony among them. This novel recounts the experiences and emotions of people in different states of India. This is a story about a girl and a boy from different states with the different cultures and caste system. They fall in love but have to face hardships in convincing their parents to support their marriage. In Indian culture, they cannot defy their parents’ consent. A boy and a girl named Krish and Ananya want to change their love into marriage but it is as a Herculean task for them because of the cultural differences between two societies. Finally, they get success to change their dream into reality only through the true love, as it is the facilitator of interpersonal relationships. Indeed, love keeps human beings together against threats, breaks the barriers and harmonizes their dissimilarities. Based on this line, this article discusses Bhagat’s 2 States and proves the love as a boundary breaker of dissimilar cultures.